2013
DOI: 10.1039/c2cc38145a
|View full text |Cite
|
Sign up to set email alerts
|

Tandem ammonia borane dehydrogenation/alkene hydrogenation mediated by [Pd(NHC)(PR3)] (NHC = N-heterocyclic carbene) catalysts

Abstract: [Pd(NHC)(PR(3))] complexes were shown to be active catalysts in the dehydrogenation of ammonia borane and the subsequent hydrogenation of unsaturated compounds at very low catalyst loadings (0.05 mol% for some substrates).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 34 publications
2
19
0
1
Order By: Relevance
“…[1,2] due to the current interest in the hydrogen storage, which is still one of the key problems in the "Hydrogen Economy" [3][4][5]. Additionally, the importance of catalytic dehydrogenation of amine-borane adducts in the polymer synthesis [6,7], tandem dehydrogenation-hydrogenation [8,9], and transfer hydrogenation [10] has also made a prominent contribution to the progress in this field. Of particular importance are the results of recent studies [viii-x] revealing that amine-boranes can be used as easily transportable sources of hydrogen for the catalytic hydrogenation of C-C multiple bonds (1), which is one of the most important processes in the organic chemistry [11].…”
Section: Introductionmentioning
confidence: 97%
“…[1,2] due to the current interest in the hydrogen storage, which is still one of the key problems in the "Hydrogen Economy" [3][4][5]. Additionally, the importance of catalytic dehydrogenation of amine-borane adducts in the polymer synthesis [6,7], tandem dehydrogenation-hydrogenation [8,9], and transfer hydrogenation [10] has also made a prominent contribution to the progress in this field. Of particular importance are the results of recent studies [viii-x] revealing that amine-boranes can be used as easily transportable sources of hydrogen for the catalytic hydrogenation of C-C multiple bonds (1), which is one of the most important processes in the organic chemistry [11].…”
Section: Introductionmentioning
confidence: 97%
“…[10c] In this reaction it was observed that the startingm aterial 1a underwent complete conversion.I nspired by this promising result,a nd our comprehension from the previous controls, we tried different triaryl phosphines. All, electronicallys imilar, electron-withdrawing (p-fluoro) and electron-donating (p-OMe) substituents on the triaryl phosphines gave exclusive hydroborylated product 4a (entries [6][7][8]. Even the cis-enforcing bidentate phosphine ligands, either failed or gave trace amounts of the expected product 2a (Table 1, entries 9-10).…”
Section: Introductionmentioning
confidence: 99%
“…Next, we probed the fate of 1 theoretically in the presence of Lewis acids B(C 6 F 5 ) 3 and B(C 6 H 5 ) 3 in nondonor solvents such as benzene. There are experimental studies in which the dehydrogenation of 1 is performed in nonpolar solvents such as benzene and toluene . In benzene, both B(C 6 F 5 ) 3 and B(C 6 H 5 ) 3 exist as free Lewis acids as benzene has no donor atom to form a Lewis acid–base adduct.…”
Section: Resultsmentioning
confidence: 99%